2008
DOI: 10.1161/strokeaha.107.503094
|View full text |Cite
|
Sign up to set email alerts
|

Importance of In-Hospital Initiation of Therapies and Therapeutic Inertia in Secondary Stroke Prevention

Abstract: Background and Purpose-Many patients do not receive prevention consistent with recommendations after stroke, but the relative importance of patient-and physician-related factors is uncertain. Methods-We prospectively assessed factors associated with blood pressure (BP) Ͻ140/90 mm Hg and low-density lipoprotein (LDL) cholesterol Ͻ1 g/L in a collaborative cohort of 240 consecutive patients experiencing stroke/transient ischemic attack (Rankin Ͻ4; Յ80 years; no major comorbidity) from a stroke unit and 3 emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 42 publications
(41 reference statements)
2
50
0
Order By: Relevance
“…1,[3][4][5][6] The identification and control of modifiable vascular risk factors (MRFs) is one of the main goals of stroke prevention clinics (SPCs) in addition to appropriate use of antithrombotics and selective surgical interventions as suggested by current practice guidelines. 1,6,7 Unfortunately, a relatively high proportion of patients fail to achieve the recommended therapeutic objectives. [8][9][10] Recent evidence in the literature suggests that improving outpatient care through referral to SPCs may decrease risk of adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1,[3][4][5][6] The identification and control of modifiable vascular risk factors (MRFs) is one of the main goals of stroke prevention clinics (SPCs) in addition to appropriate use of antithrombotics and selective surgical interventions as suggested by current practice guidelines. 1,6,7 Unfortunately, a relatively high proportion of patients fail to achieve the recommended therapeutic objectives. [8][9][10] Recent evidence in the literature suggests that improving outpatient care through referral to SPCs may decrease risk of adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for this gap between guideline recommendations and current practise are not well known. The most commonly cited factors include patient nonadherence to prescribed treatment, therapeutic inertia (defined as the lack of initiating or intensifying treatment despite failure to achieve therapeutic goals) and lack of access to care [11,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…17 The true benefit is likely from improved processes of care in the short term that lead to long-term improvement in outcomes. 4,5,18 Thus, the advantage of starting a patient hospitalized for a stroke on blood pressure medication is the increased likelihood that the patient will continue the medication as an outpatient, which may reduce long-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that intervening in chronic diseases during hospitalizations can lead to long-term improvement in treatment; [4][5][6] for instance, stroke patients who were started on antihypertensive therapy at discharge were more likely to have their blood pressure controlled in the next year. 5 However, some authors have argued that aggressive hypertension management by inpatient providers may result in patient harm. 7 One case-based survey suggested that hospitalists were mixed in their interest in participating in chronic disease management in the hospital.…”
mentioning
confidence: 99%